The Effect of Background Noise on a “Studying for an Exam” Task in an Open-Plan Study Environment: A Laboratory Study - Braat-Eggen, Ella; Reinten, Jikke; Hornikx, Maarten; Kohlrausch, Armin (Frontiers in Built Environment, 2021)
Students can be disturbed by background noise while working in an open-plan study environment. To improve the acoustic quality of open-plan study environments a study was done on the influence of different sound scenarios on students working on a typical student task, 'studying for an exam'. Three sound scenarios and a quiet reference sound scenario were developed, based on the sound environment of a real open-plan study environment, with a varying number of talkers in the background and different reverberation times of the study environment. Seventy students worked on a set of tasks simulating a 'studying for an exam' task while being exposed to the sound scenarios. This task comprises a reading comprehension task with text memory by delayed answering questions about the text, with additional tasks being performed in the gap between studying the text and retrieving. These additional tasks are a mental arithmetic task and a logical reasoning task. Performance, self-estimated performance and disturbance of students were measured. No significant effect of the sound scenarios was found on performance of students working on the reading comprehension task with text memory and the mental arithmetic task. However, a significant effect of sound was found on performance of students working on the logical reasoning task. Furthermore, a significant effect of the sound scenarios was found on self-estimated performance and perceived disturbance for all tasks from which the reading comprehension task with text memory was the most disturbed task. It is argued that the absence of a detrimental sound effect on the performance of students working on a reading comprehension task with text memory is a result of focusing due to task engagement and task difficulty, both aspects working as a 'shield against distraction'.